2012
DOI: 10.1103/physrevb.86.014410
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the ground state of La0.67Ca0.33MnO3films via coherent gr

Abstract: The commensurate La 0.67 Ca 0.33 MnO 3 films, of which the bulk is a ferromagnetic-metal (FM), can show strikingly different ground states when grown on NdGaO 3 substrates of various orientations. With a larger orthorhombic lattice distortion in the substrates, the (110) films can grow essentially strain-free, but the (100) and (001) films are anisotropically strained, accompanied by an increased orthorhombicity. As a result, while the (110) films show constantly a bulklike FM ground state, the others behave d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…In fact, by comparing the magnetotransport properties of LCMO films grown on the NGO substrates with various orientations, we have excluded the interfacial chemical diffusion and variation of La:Ca doping ratio during ex-situ annealing, and demonstrated that the AFI phase is elastic-driven. 33,35 In Fig. 1(c), the ω-2θ linear scans of the 10-h annealed films (20 and 40 nm) show sharp Laue fringes, further confirming that the LCMO films have high crystal quality and sharp interface with the underlying substrates.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…In fact, by comparing the magnetotransport properties of LCMO films grown on the NGO substrates with various orientations, we have excluded the interfacial chemical diffusion and variation of La:Ca doping ratio during ex-situ annealing, and demonstrated that the AFI phase is elastic-driven. 33,35 In Fig. 1(c), the ω-2θ linear scans of the 10-h annealed films (20 and 40 nm) show sharp Laue fringes, further confirming that the LCMO films have high crystal quality and sharp interface with the underlying substrates.…”
Section: Resultsmentioning
confidence: 63%
“…34,35 With decreasing the thickness to 20 nm, the annealed film shows a higher ρ below T AFI , indicating an enhanced AFI phase. In fact, by comparing the magnetotransport properties of LCMO films grown on the NGO substrates with various orientations, we have excluded the interfacial chemical diffusion and variation of La:Ca doping ratio during ex-situ annealing, and demonstrated that the AFI phase is elastic-driven.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations